Anterior Cruciate Ligament Injury Preventive Program for Soccer Female Players During Confinement Periods - Calvo-Fernández, Yonathan; Lago-Rodríguez, Ángel (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2022)
The COVID-19 pandemic resulted in a worldwide sports shutdown, leading to a reduced athletes’ workload, which is likely to increase the risk of injury after return to play when coupled with the expected increase in competitive density after the confinement period. In this regard, the knee is one of the joints with the highest injury prevalence among female soccer players, being the injury of the anterior cruciate ligament (ACL) one of the most frequent and severe. Thus, the present study aimed to develop an ACL injury prevention program that female soccer players could carry out during confinement periods. After reviewing the scientific literature, it was observed that strength training (with a main focus on the posterior chain), improved landing technique, lumbopelvic stability, and flexibility are associated with a lower risk of ACL injury in women. The program focuses on modifiable risk factors, so it should serve as a guide that can be adapted according to each context: individual characteristics, initial conditions, and evolution of the subject during development. Therefore, this study presents an intervention aiming at reducing the probability of ACL injury in female soccer players, after confinement periods, by directly influencing mechanisms of ACL injury previously reported for female soccer players.